Widely contrasting outcomes from the use of tris(pentafluorophenyl)bismuth or pentafluorophenylsilver as oxidants in the reactions of lanthanoid metals with N, N′-diarylformamidines. Issue 39 (24th September 2020) - Guo, Zhifang; Blair, Victoria L.; Deacon, Glen B.; Junk, Peter C.
Abstract : Reactions of lanthanoid metals with Bi(C6 F5 )3 or AgC6 F5 and two widely disparate formamidines, have been investigated. Abstract : Reactions of lanthanoid metals with tris(pentafluorophenyl)bismuth or pentafluorophenylsilver and two widely disparate formamidines, N, N ′-bis(2, 6-difluorophenyl)formamidine (DFFormH) and N, N ′-bis(2, 6-diisopropylphenyl)formamidine (DippFormH) have been investigated as possible redox transmetallation/protolysis (RTP) syntheses of lanthanoid formamidinates. Thus, [Ln(DFForm)3 (thf)] (Ln = Lu, 1, Yb, 2, Tm, 3, Er, 4, Ho, 5, Dy, 6 ; thf = tetrahydrofuran), [Ln(DFForm)3 (thf)2 ] (Ln = Tb, 7, Gd, 8, Sm, 9, Nd, 10 ), and [Yb(DippForm)2 (thf)2 ]·2thf (11 ) complexes were obtained from an excess of lanthanoid metals, [Bi(C6 F5 )3 ]·0.5diox (diox = 1, 4-dioxane) and the appropriate formamidine. Reaction of neodymium and [Bi(C6 F5 )3 ]·0.5diox with the bulkier DippFormH in thf resulted in C–F activation and formation of [Nd(DippForm)2 F(thf)2 ] (12 ) and o -HC6 F4 O(CH2 )4 N(Dipp)CHN(Dipp) (Dipp = 2, 6-di-isopropylphenyl). Although the reaction of erbium and [Bi(C6 F5 )3 ]·0.5diox with DippFormH was not complete after one week (by 19 F NMR), use of [Hg(C6 F5 )2 ] instead of [Bi(C6 F5 )3 ]·0.5diox resulted in C–F activation and formation of [Er(DippForm)2 F(thf)] (13 ) and o -HC6 F4 O(CH2 )4 N(Dipp)CHN(Dipp) in two days. Attempted RTP reactions between lanthanoid metals, AgC6 F5 and DFFormH in thf gave [Ag2 (DFForm)2 ]·3thf (14 ), except in the case of ytterbium. All other lanthanoid metals required activation by I2 (2%) before lanthanoid complex formation could be achieved. From these reactions, lanthanoid formamidinates, [Ln(DFForm)2 (solv)I] (Ln = Lu, 15, Tm, 16, Er, 17, Tb, 18, Gd, 19 ), [Ln(DFForm)3 (py)] (Ln = Er, 17a, Tb, 18a ; py = pyridine), and [Nd(DFForm)3 (thf)2 ]·thf (10 ) were obtained. Where two types of lanthanoid formamidinates [Ln(DFForm)3 (py)] and [Ln(DFForm)2 (solv)I] were obtained from the Ln metals activated by I2, they could not be separated on preparative scale. From Yb, the peroxide-bridged complex, [Yb2 (DippForm)2 (O2 )2 (py)4 ] (20 ) was surprisingly isolated. Thus [Bi(C6 F5 )3 ]·0.5diox has potential as an oxidative replacement for diarylmercurials in RTP syntheses of lanthanoid formamidinates but [AgC6 F5 (py)] does not.